2002
DOI: 10.1055/s-2002-33216
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment by Argon Plasma Coagulation of Bleeding Radiation-Induced Gastroduodenal Vasculopathy

Abstract: Gastroduodenal vasculopathy is a rare but well-known complication of upper gastrointestinal radiation treatment [1]. Although argon plasma coagulation (APC) has been shown to be effective and safe in the management of radiation-induced rectal bleeding [2] and watermelon stomach [3], the use of APC has not been reported for diffuse radiation vascular lesions located in the upper gastrointestinal tract.In 1999, an 80-year-old man was treated for a cholangiocarcinoma by endoscopic biliary metal stenting and exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…reported a patient with radiation‐induced carditis who was successfully treated with APC in 2000. Although many investigators have confirmed the value of APC in treating many cases of radiation‐induced proctosigmoiditis (Table 1), 4–9 only two instances of APC therapy for radiation‐induced gastritis have been reported 3,10 . Although the distribution of these two patients’ gastritis differed from that of typical radiation‐induced gastritis after EBRT for bile duct cancer, APC ensured a better prognosis, as evident in our current cases.…”
Section: Previously Reported Study Of Argon Plasma Coagulation (Apc)supporting
confidence: 44%
“…reported a patient with radiation‐induced carditis who was successfully treated with APC in 2000. Although many investigators have confirmed the value of APC in treating many cases of radiation‐induced proctosigmoiditis (Table 1), 4–9 only two instances of APC therapy for radiation‐induced gastritis have been reported 3,10 . Although the distribution of these two patients’ gastritis differed from that of typical radiation‐induced gastritis after EBRT for bile duct cancer, APC ensured a better prognosis, as evident in our current cases.…”
Section: Previously Reported Study Of Argon Plasma Coagulation (Apc)supporting
confidence: 44%
“…Many investigators have confirmed the value of argon plasma coagulation in treating numerous cases of radiationinduced proctosigmoiditis, 2-7 but only a few instances of argon plasma coagulation therapy for radiation-induced gastritis have been reported. [8][9][10] To our knowledge, the efficacy of EBL in this location has not been reported.…”
Section: Discussionmentioning
confidence: 85%
“…The limited depth of coagulation explains the low risk of perforation [14]. Many investigators have confirmed the therapeutic value of APC in cases of HRG [15][16][17]; APC seems to be suitable for thermal coagulation of HRG. Although our patient received five applications of APC over a month, the bleeding continued, and the patient still showed persistent and progressive anemia.…”
Section: Discussionmentioning
confidence: 97%